Pengambilan Keputusan Orang Tua Mengenai Vaksinasi HPV Untuk Remaja Perempuan - Hamka, Hamka; Yusuf, Rezky Aulia; Sumarmi, Sumarmi (Jurnal Keperawatan Muhammadiyah, 2024)
Background: Cervical cancer ranks second in prevalence in women in Indonesia. Human Papillomavirus (HPV) vaccination has been proven effective in reducing the incidence and mortality from cervical cancer. HPV vaccination has been available in Indonesia since 2022 and the Indonesian Government is targeting 90% of girls to receive HPV immunization by 2030. The decision to vaccinate adolescent girls is generally left to parents. This study applies the Theory of Planned Behavior (TPB) to predict parents' desires and behaviors in carrying out HPV vaccination. Objective: This study aims to predict HPV vaccination behavior in parents who have adolescent daughters. Methods: A prospective study design was conducted for 3 months. 130 participants were recruited from 5 elementary schools in Takalar Regency, Indonesia by convenience sampling. Participants involved in this study were parents who have adolescent daughters, adolescent girls aged 11-12 years and are able to speak Indonesian, both literate and illiterate. The exclusion criteria were adolescent girls who were allergic to one of the ingredients in the HPV vaccination. Questionnaires used in this study such as the Health Behavior Survey HPV Vaccination Subscale, demographic data, and related health factors. Logistic regression was used to confirm the causal relationship of variables and to test the TPB constructs. Results: The final logistic regression model of undergoing HPV vaccination included the variables: parental income (OR: 4.60, 95% CI: 1.10 - 9.01). Conclusion: The results of this study indicate a relationship between parental income and HPV vaccination behavior.